Export creation of the Belt and Road Initiative: “Give‐them‐a‐fish” or “Teach‐them‐to‐fish”? - Yu Chen; Yan Zhang; Lin Zhao (International Studies of Economics)
Abstract The Belt and Road Initiative (BRI) initiated by China in 2013 is a new experiment in regional cooperation, which aims to improve infrastructure connectivity through investment. This paper investigates whether the BRI created exports for its member states (excluding China), based on a difference‐in‐differences model. We find a significant causal relationship between the signing of the initiative and the export growth of its member states. In addition to the large export creation between the BRI countries and China (considered as “give‐them‐a‐fish”), export creation also originated from the BRI countries excluding China (“teach‐them‐to‐fish”). Both the intensive and extensive margins are significantly important, indicating that export creation has not just come from expansion of the volume of existing products, but also from new products and new markets. The BRI achieved the goal of mutual benefit mainly through enlisting investment in both publicly funded infrastructure sectors and private sectors. Moreover, the initiative has enhanced the position and participation of its member states in the global value chain.